Children's performance in reading and writing Bangla: a comparison between BRAC and formal school - Nath, Samir Ranjan (BRAC Research and Evaluation Division (RED), 2020)
This report aims to compare the performance of the learners of non-formal schools of BRAC and formal schools in reading and writing Bangla Data were collected from five areas where a surveillance system was in operation. A sample of 480 children, equally distributed by study groups and sex. were randomly selected. This study reveals that NFPE graduates were more likely to have better skills in writing and overall t:est compared to their peers in formal schools. However, in reading both. the groups performed equally well. Measures such as proper training of teachers, regular parent-teacher meeting, and intensive supervision and monitoring of teaching learning activities may be a key to improve the overall education situation in Bangladesh.